Alternative Lithographic Technologies V 2013
DOI: 10.1117/12.2012488
|View full text |Cite
|
Sign up to set email alerts
|

Healing LER using directed self assembly: treatment of EUVL resists with aqueous solutions of block copolymers

Abstract: Overcoming the resolution-LER-sensitivity trade-off is a key challenge for the development of novel resists and processes that are able to achieve the ITRS targets for future lithography nodes. Here, we describe a process that treats lithographic patterns with aqueous solutions of block copolymers to facilitate a reduction in LER. A detailed understanding of parameters affecting adhesion and smoothing is gained by first investigating the behavior of the polymers on planar smooth and rough surfaces. Once healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This emphasizes the potential of EUV lithography as the next leading technology for semiconductor device manufacturing by obeying Moore's law. To expand the application of EUV lithography, new process techniques were proposed, such as the combination of EUV lithography and directed self-assembly [1][2][3][4] and negative tone development (NTD) [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the potential of EUV lithography as the next leading technology for semiconductor device manufacturing by obeying Moore's law. To expand the application of EUV lithography, new process techniques were proposed, such as the combination of EUV lithography and directed self-assembly [1][2][3][4] and negative tone development (NTD) [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Healing of LER following development is another approach that has led to significant improvements in LER. [27,28] On the other hand, directed self assembly (DSA) of block copolymers is a technique that has demonstrated significant promise for achieving high resolution. DSA is a technique that brings together lithography (top-down) to fabricate patterns that guide the self assembly of diblock copolymers (bottom-up).…”
Section: Introductionmentioning
confidence: 99%
“…Use of directed self-assembly (DSA) of block copolymer is another approach to healing LER [11,12]. It has been shown that the highly ordered patterns of immiscible blocks formed by DSA depending on the relative volume fraction of each block, the total molecular weight, and the degree of immiscibility, have smaller LER than the lithographic features that were used to guide them [43].…”
Section: Figure-113mentioning
confidence: 99%